The Effect of Individual Characteristics and Work Ethic on Employee Performance Trough Organization Commitment as Mediaton in Public Sector - Endartanto Endartanto; Kusuma Candra Kirana; Syamsul Hadi (UNIVED Press, 2024)
The purpose of this study was to determine the effect of individual characteristics and work ethic on performance with organizational commitment as a mediating variable. This research is a quantitative study using saturated samples whose population of BPKPSDM Bantul Regency is 55 employees. The results of the study Individual Characteristics have a positive but insignificant effect on Organizational Commitment, Work Ethic has a significant positive effect on Organizational Commitment, Individual Characteristics have a positive but insignificant effect on Performance, Work Ethic has a positive but insignificant effect on Performance, Organizational Commitment cannot act as a mediating variable between Individual Characteristics on Performance, Organizational Commitment can act as a mediating variable between Work Ethic on Performance.